Being the boss : the 3 imperatives for becoming a great leader - Hill, Linda A. 1956- (Harvard Business Review Press, 2019)
Are you the boss you need to be' You never dreamed being the boss would be so hard. You're caught in a web of conflicting expectations from your subordinates, from those above you, and from your peers and customers. You're not alone. As Harvard Business School's Linda Hill and manager and executive Kent Lineback reveal in Being the Boss, becoming an effective manager is a painful, difficult journey. It requires trial and error, endless effort, and slowly acquired personal insight. Many managers never complete the journey and instead just learn how to get by. At worst, they become terrible bosses. This essential book, now with a new preface, explains how to avoid that fate by mastering three imperatives: -Manage yourself: Learn that management isn't about doing all the work on your own. It's about leading others to accomplish things with you as their guide. -Manage your network: Understand how power and influence work in your organization, and build a network of mutually beneficial relationships to navigate your company's complex political environment -Manage your team: Create a high-performing "we" out of all the "I's" who report to you. Packed with compelling stories and practical advice, Being the Boss is an indispensable guide not only for first-time managers but for all managers seeking to master the most daunting challenges of leadership.